Upper bounding service capacity in multi-hop wireless SSMA-based ad hoc networks - Du, Shirong; Daigle, John N.; Alidaee, Bahram (Ad hoc networks, 2011)
Upper bounds on the service carrying capacity of a multi-hop, wireless, SSMA-based ad hoc network are considered herein. The network has a single radio band for transmission and reception. Each node can transmit to, or receive from, multiple nodes simultaneously. We formulate the scheduling of transmissions and control of transmit powers as a joint, mixed-integer, nonlinear optimization problem that yields maximum return at minimum power subject to SINR constraints. We present an efficient tabu search-based heuristic algorithm to solve the optimization problem and rigorously assess the quality of the results. Through analysis and simulation, we establish upper bounds on the VoIP call carrying capacity of the network as function of various parameters. We discuss the pros and cons of using SSMA as a spectrum sharing technique in wireless ad hoc networks.